2020
DOI: 10.21203/rs.2.18446/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and outcomes of a comprehensive multidisciplinary incidental lung nodule and lung cancer screening program

Abstract: Background: Appropriate management of lung nodules detected incidentally or through lung cancer screening can increase the rate of early-stage diagnoses and potentially improve treatment outcomes. However, the implementation and management of comprehensive lung nodule programs is challenging. Methods: This single-center, retrospective report describes the development and outcomes of a comprehensive lung nodule program at a community practice in Tennessee. Computed tomography (CT) scans potentially revealing in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The study results by Osarogiagbon et al, 19 coupled with those previously published, 20,21 highlight the complementary benefits of two multidisciplinary approaches, LCS and ILN programs, for early detection of lung cancer. First, in previous studies, 20,21 most nodules were detected incidentally, supporting the importance of an established ILN program to implement guideline-concordant management of incidental nodules that may represent early-stage lung cancer. Second, in the study by Osarogiagbon et al, 19 most patients diagnosed with lung cancer in the ILN program were not eligible for screening by 2021 USPSTF criteria.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…The study results by Osarogiagbon et al, 19 coupled with those previously published, 20,21 highlight the complementary benefits of two multidisciplinary approaches, LCS and ILN programs, for early detection of lung cancer. First, in previous studies, 20,21 most nodules were detected incidentally, supporting the importance of an established ILN program to implement guideline-concordant management of incidental nodules that may represent early-stage lung cancer. Second, in the study by Osarogiagbon et al, 19 most patients diagnosed with lung cancer in the ILN program were not eligible for screening by 2021 USPSTF criteria.…”
supporting
confidence: 54%
“…Previous studies have reported the benefits of concurrent multidisciplinary LCS and ILN programs. 20,21 A study of over 1,000 patients, of which 89.2% were White, seen at a multidisciplinary LCS and ILN management clinic, showed that (1) the majority (80%) of nodules were detected incidentally, (2) nearly 95% of patients diagnosed with lung cancer had early-stage disease, (3) a shorter time to diagnosis, < 50 days, and (4) significantly higher adherence rate to diagnostic and treatment recommendations. However, the low proportion of minority patients in the study limited generalizability, hampering the ability to assess the impact of the parallel programs on racial and ethnic disparities in lung nodule management.…”
mentioning
confidence: 99%
See 1 more Smart Citation